The N-terminus of survivin is a mitochondrial-targeting sequence and Src regulator - Dunajova, Lucia; Cash, Emily; Markus, Robert; Rochette, Sophie; Townley, Amelia R.; Wheatley, Sally P. (The Company of Biologists, 2016)
Survivin is a cancer-associated protein that exists in several locations in the cell. Its cytoplasmic residence in interphase cells is governed by CRM1-mediated nuclear exportation, and its localisation during mitosis to the centromeres and midzone microtubules is that of a canonical chromosomal passenger protein. In addition to these well-established locations, survivin is also a mitochondrial protein, but how it gets there and its function therein is presently unclear. Here we show that the first 10 amino acids at the NH2 terminus of survivin are sufficient to target GFP to the mitochondria in vivo, and ectopic expression of this decapeptide decreases cell adhesion and accelerates proliferation. The data support a signalling mechanism in which mitochondrial survivin activates the tyrosine kinase, C-Src, leading to reduced focal adhesion plaques and disruption of F-actin organisation. This strongly suggests that the NH2 terminus of survivin is a mitochondrial targeting sequence that regulates C-Src, and that survivin acts in concert with C-Src to promote tumorigenesis.